DAMPAK PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP PENDAPATAN COFFEE SHOP DI KOTA DENPASAR - Fany Fadilla; I Made Endra Kartika Yudha (Universitas Udayana, 2023)
The Denpasar City Government's great support for MSMEs is one of them provided through the Denpasar City Cooperatives and MSMEs Office. The support provided is in the form of providing education and training to MSMEs in Denpasar City. One of the developing Micro Small Medium Enterprises is the Coffee Shop. The aims of this research are to analyze the difference in Coffee Shop income before and after attending education and training (Training) by the Cooperative and MSME Office of Denpasar City, and to find out the perceptions of Coffee Shop business owners towards the provision of education and training (training) by the Office of Cooperatives and SMEs in Denpasar City. The study employed a saturated sampling technique with a sample size of 35 respondents due to the small population size. Data were collected through observations, structured interviews, and in-depth interviews. The data analysis involved the utilization of a comparative test. The findings of the research indicated a notable disparity in the revenue of coffee shops prior to and following their participation in the education and training initiative. This is in line with the purpose of providing education and training, which aims to enhance the skills and knowledge of business owners in managing their coffee businesses. By improving their skills, business owners can enhance operational efficiency and effectiveness, leading to increased productivity and income. keyword: Education and Training, MSMEs, Coffee Shop, Income